Religious Behavior Development in the 4.0 Era: The Islamic Education Challenges - Nurhasanah, Anah (Bestari, 2024)
The digital age, or Era 4.0, has induced substantial transformations in religious practices and religious education. This paper intends to elucidate the effects of this transition and emphasize the significance of religious education in addressing the ensuing issues. Era 4.0 influences how individuals obtain knowledge, navigate value conflicts, and assimilate into contemporary culture. This paper employs a qualitative methodology grounded in literature analysis. This methodology is suitable for conceptual research of this nature. The literature study approach involves gathering data through the identification and examination of pertinent written sources related to the research topic. The study's findings indicate that, in light of these changes, educators play a crucial role in equipping students to confront a future characterized by transformation. This article emphasizes the significance of 21st-century capabilities in religious education, effective presentation of content aligned with students' interests, and the use of creative, authentic learning techniques. In summary, religious education and the function of educators in navigating the digital age are essential for assisting persons in comprehending and mitigating its effects on religious conduct, thereby equipping them for an evolving future.